Translating a whole of system approach to an urban community setting: a realist evaluation. (30th September 2020) - Maitland, N; Wardle, K; Haigh, F; Allender, S; Jalaludin, B
Abstract: Introduction: The recent Lancet Commissions report on The Global Syndemic of Obesity, Undernutrition, and Climate Change highlights the need for comprehensive actions to address the global epidemic of obesity. The Campbelltown - Changing our Future project utilised a community led participatory systems mapping approach to develop interventions to address childhood obesity in an urban environment. While there is evidence demonstrating the impact of systems approaches on outcomes, there is limited examples internationally demonstrating what works in which circumstances, for whom and most importantly how. Methods: A realist evaluation framework was used by project staff to identify key mechanisms that enabled project outcomes. This framework uses four key interrelated concepts: "mechanism", "context", "outcome pattern" and "context-mechanism-outcome (CMO) pattern configuration". Five key underlying properties that influenced the project were analysed using the CMO pattern configuration. Results: The five key properties that the project team has identified as key influences in the translation of a whole of system approach in an urban community are: endorsement, ways of working, deliberative learning, personality traits and partnerships. These mechanisms enabled over 90 community-led actions to be established. Conclusions: The five properties work harmoniously together when performed in an enabling context to produce comprehensive, community-led action. Understanding "how" these theories interact and the optimal context provides opportunity for a broader understanding on the process of practical implementation of a whole of system approach. Key messages: Provides insight into how a practical example of a whole of system approach is implemented. Endorsement, flexible ways of working, deliberative learning, personality traits and partnerships are enablers of systems based participatory approaches addressing obesity within a community setting.